The fishes of St Helena Island, central Atlantic Ocean—new records and an annotated check-list - Brown, Judith; Beard, Annalea; Clingham, Elizabeth; Fricke, Ronald; Henry, Leeann; Wirtz, Peter (Zootaxa, 2019)
A check-list of the fishes of St Helena Island is presented. The following species are recorded for the first time from St. Helena Island: Rhincodon typus, Mobula tarapacana, Muraena melanotis, Caranx latus, Seriola rivoliana, Balistes capriscus, Lutjanus jocu, Centropyge aurantonotus, Acanthurus coeruleus, Lepidocybium flavobrunneum, Tetrapturus pfluegeri, Coelorinchus geronimo, Pentaceros richardsoni, Gephyroberyx darwinii, Brotula cf multibarbata, Poromitra crassiceps, Echiostoma barbatum, Malacosteus niger, Pachystomias microdon. Including these nineteen new records there are 189 fish species currently known from St Helena. Three of them appear to be undescribed. Eight species and two subspecies are currently considered endemic to St. Helena Island.